Highly efficient delivery of functional cargoes by the synergistic effect of GAG binding motifs and cell-penetrating peptides - Dixon, James E.; Osman, Gizem; Morris, Gavin E.; Markides, Hareklea; Rotherham, Michael; Bayoussef, Zahia; El-Haj, Alicia; Denning, Chris; Shakesheff, Kevin M. (National Academy of Sciences, 2016)
Protein transduction domains (PTDs) are powerful nongenetic tools that allow intracellular delivery of conjugated cargoes to modify cell behavior. Their use in biomedicine has been hampered by inefficient delivery to nuclear and cytoplasmic targets. Here we overcame this deficiency by developing a series of novel fusion proteins that couple a membrane-docking peptide to heparan sulfate glycosaminoglycans (GAGs) with a PTD. We showed that this GET (GAG-binding enhanced transduction) system could deliver enzymes (Cre, neomycin phosphotransferase), transcription factors (NANOG, MYOD), antibodies, native proteins (cytochrome C), magnetic nanoparticles (MNPs), and nucleic acids [plasmid (p)DNA, modified (mod)RNA, and small inhibitory RNA] at efficiencies of up to two orders of magnitude higher than previously reported in cell types considered hard to transduce, such as mouse embryonic stem cells (mESCs), human ESCs (hESCs), and induced pluripotent stem cells (hiPSCs). This technology represents an efficient strategy for controlling cell labeling and directing cell fate or behavior that has broad applicability for basic research, disease modeling, and clinical application.